2006
DOI: 10.1002/ejlt.200600078
|View full text |Cite
|
Sign up to set email alerts
|

Structure evolution and bloom formation in tempered cocoa butter during long‐term storage

Abstract: Structure evolution and bloom formation in tempered cocoa butter during long-term storageStructural evolution in tempered cocoa butter (CB) and CB mixed with a cocoa butter equivalent (CBE) was examined during 26 wk of storage (at 25 7C) using atomic force microscopy, X-ray powder diffraction, colorimetry and pulsed nuclear magnetic resonance. The form V-to-VI polymorphic transition in CB started after 1 week of storage. However, fat bloom was not detected until week 3 when large crystals started to appear on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 18 publications
(27 reference statements)
1
44
0
Order By: Relevance
“…This is perhaps due to the more complex crystalline forms (polymorphic structures) provided by modified oil (EIS) in the chocolate sample (Osborn and Akoh, 2002). This result is similar to that of Sonwai and Rousseau (2006), who reported that addition of cocoa butter equivalent to chocolate formulation delays bloom development by 1~2 weeks. Our finding is also in agreement with Osborn and Akoh (2002).…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…This is perhaps due to the more complex crystalline forms (polymorphic structures) provided by modified oil (EIS) in the chocolate sample (Osborn and Akoh, 2002). This result is similar to that of Sonwai and Rousseau (2006), who reported that addition of cocoa butter equivalent to chocolate formulation delays bloom development by 1~2 weeks. Our finding is also in agreement with Osborn and Akoh (2002).…”
Section: Resultssupporting
confidence: 74%
“…Values L*, a* and b* were measured using a Hunter-Lab colorimeter (Hunter Associated Laboratory, Inc., Reston, Virginia, USA) and converted to whiteness index (WI) values according to the following equation (Sonwai and Rousseau, 2006): An X-ray diffractometer (Philips, X' pert, The Netherlands) equipped with a CuKα (λ=1.54 Å) radiation source was employed to determine the polymorphic forms of the samples. The instrument setting was 40 kV with filament currents of 40 mA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The recommended fat blend from the above section was mixed with CB in a ratio of 5.64:1 (wt) for CB/CBE which mimicked that of typical dark chocolate where 5 % of CBE is added to the finished product (Sonwai and Rousseau 2006). Assuming that the total fat content of typical dark chocolate is 33.2 %wt of the final product, chocolate that contains 5 % CBE will contain 28.2 % CB and this will give a ratio of 5.64:1 for CB/CBE in the product.…”
Section: Crystallization Behavior Under Static Isothermal Conditionmentioning
confidence: 99%
“…The samples were tempered using a procedure described elsewhere (Sonwai and Rousseau 2006), then moulded into solidified discs (diameter 0 30 mm, thickness 3 mm) and put inside a temperature-controlled cabinet. L*, a* and b* values of the moulded side of the samples were measured once every week and converted to WI values using Eq.…”
Section: Fat Bloom Studymentioning
confidence: 99%